The Role of Gender in the Apology Strategies of Advanced Saudi EFL Students - GONI, FAWZIA (2017)
Apologies vary across languages and cultures. Therefore, EFL and ESL teachers and learners must be cognizant of the similarities and differences between the target language and the native language, because what might be acceptable in one language might not be acceptable in the other language. The purpose of this study is to examine whether gender plays a role in the apology strategies employed by 20 male and 20 female advanced Saudi EFL university students. Data were elicited using a Discourse Completion Task questionnaire (DCT), comprising of 10 real-life situations in the form of short descriptive statements which required the respondents to make an apology. Questions in the DCT varied according to the level of imposition and the distance between the interlocutors. Only gender was examined as a variable. Participants’ responses were analyzed in accordance with a combination of Cross-Cultural Speech Act Realization Patterns (CCSARP) Blum- Kulka & Olshtain’s (1984, 1989) and Cohen and Olshtain’s (1981) apology strategies. Therefore, the responses were classified into five distinct apology strategies: Illocutionary Force Indicating Device (IFID), Responsibility (RESP), Explanation (EXPL), Repair (REPR), and Forbearance (FORB). The results reveal that gender plays a significant role in the apology strategies used by the respondents. Similarities and differences were also observed in the use of apology strategies. The study findings reveal that both men and women used the main apology strategies, but with different degrees, clearly indicative of the fact that women in Saudi Arabia apologized more than men. This can be interpreted as the influence of cultural gender roles. The researcher concludes with possible pedagogical implications and recommendations for further research.